Development of a Smart Charging and Switching System for a Low-Voltage Air Circuit Breaker - Balasundram, Vijay; Md Nor Ramdon Baharom; Zainab Zainal; Azuwien Aida Bohari; Sim Sy Yi (Progress in Engineering Application and Technology, 2024)
Air circuit breakers (ACB) interrupt electric current in electrical circuits. It protects electrical equipment from overcurrent and short circuits. Different applications require different ACB sizes and grades. A competent electrician manually pumps and switches the ACB for troubleshooting and maintenance. The ACB may explode, making the operation risky. Typically, an electrician will manually pump and switch the air circuit breaker by touching the ACB directly. For the ACB to be charged ultimately, it needs to be pumped twelve to thirteen times, and the maximum weight the pump can produce is 27.5 kg. An electrician must use two hands to hold the charging handle to pump the charging handle of the ACB. This project presents an application using a solenoid and a mechanical mechanism consisting of a DC motor to replace this manual scope work automatically. The DC motor is used to pump the charging handle of the ACB until the indicator shows "charged." After that, the solenoid turns the ACB on and off. This system comprises components such as the NodeMCU, DC motor, two-channel relay, pushbuttons, Cytron md25hv motor driver, and solenoids. The NodeMCU is the project’s central processing unit and manages input and output. Blynk and pushbuttons can control this operation. Next, a camera is attached to monitor the operation from a distance. The goal of this system is to assist workers in the electrical field, which requires constant attention to safety because it can endanger life and even cause death. This project results in a much easier and more reliable working environment.